ANALISIS FAKTOR YANG MEMPENGARUHI PERUSAHAAN MENGAMBIL KEPUTUSAN LINDUNG NILAI (HEDGING) DENGAN INSTRUMEN DERIVATIF - Mayang Puspita Zahra; Achmad Tjahjono (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to analyze the factors that influence the decision making ofhedging with derivative instruments in manufacturing companies withMiscellaneous Industry sectors on the Indonesia Stock Exchange 2015-2018.The factors include: Leverage, Liquidity, Growth Opportunities, ManagerialOwnership, Dividend Policy The analytical method used in this study is the logisticregression method. The population of this research is the Miscellaneous IndustrySector Company. By using purposive sampling technique, there are 22 companieswith 4 years of observation from 2015-2018, obtained 88 research samples.Basedon the results of the study of the five independent variables on the dependentvariable, the variable liquidity, growth opportunity, managerial ownership showedthe results had a significant effect on hedging decisions with derivativeinstruments. Other variables such as leverage and dividend policy have nosignificant effect on hedging decisions with derivative instruments.